Alat Pemisah Telur Boleh Laras - Izzat Ziyad Zamakhshary Mustapha,; Hazrul Hamdan,; Harith Salihin Hilmi,; Sidek, Noor Azizah; Azli Nawawi, (Multidisciplinary Applied Research and Innovation, 2024)
This study aims to design an efficient manual egg yolk separator for separating egg yolks and egg whites. Currently, the traditional method of manually breaking eggs requires skill and consumes a significant amount of time. Therefore, there is a need for a more efficient and compact approach. The objectives of this study are to reduce the time required for egg breaking and yolk separation, as well as to streamline the process for large-scale egg separation. The findings of this study are expected to benefit small-scale entrepreneurs in the bakery and pastry industry and enhance productivity in the egg yolk and egg white separation process.